Influences on Adolescent Girls’ Decisions Not to Smoke Cigarettes: A Qualitative Study - Matheson, Jennifer L; Meszaros, Peggy S (Nurture, 2007)
While many studies exist on adolescent smoking, few studies have been conducted to examine what influences adolescent girls say impact their decision-making about smoking cigarettes. We purposively sampled 13 teenage girls from a rural, tobacco-producing region in Southwestern Virginia for this qualitative study. All participants reported they were current non-smokers, and they mentioned parents, peers, and the media as the most common and powerful influences on their decision-making. Girls reported receiving strong, clear messages from multiple sources about not smoking, health risks, and morality-based warnings about harm to the body. Also influential to them were grandparents, other family members, churches/spirituality, and their own sense of self. While the results of this study cannot be generalized to the larger population, they do indicate that multiple people and entities have an important role in helping some girls decide not to smoke, even when the tobacco-producing industry has been present in their community for generations.